Modelo de negocio para la creación de la empresa C&O asesorías 360 digital en asesorías contables y tributarias mediante plataformas digitales para empresarios informales en Colombia (2024)
The business plan of C&O Asesorías 360 Digital has been designed to take advantage of the opportunities offered by the digital environment in the field of accounting and tax advice. Through the use of digital platforms, the company seeks to provide an agile, accessible and quality service to informal entrepreneurs in Colombia, who represent a significant part of the country's economy. The objective of this business plan focuses on business formalization, efficiency in the provision of services and quality in the advice provided. With a focus on personalizing services, C&O Asesorías 360 Digital seeks to build solid and lasting relationships with its clients, offering solutions adapted to their specific needs. Additionally, the company is committed to staying at the forefront of accounting and tax regulations in Colombia, to ensure that its clients are always up to date and in compliance with the law. Through a team of highly trained professionals and the use of cutting-edge technology, C&O Asesorías 360 Digital positions itself as a strategic ally for informal entrepreneurs seeking to professionalize their business and ensure its long-term growth. The business plan of C&O Asesorías 360 Digital is based on innovation, quality and efficiency, with the aim of becoming a benchmark in the accounting and tax consulting market for informal entrepreneurs in Colombia. With a long-term vision and a focus on the needs of its clients, the company positions itself as an attractive and reliable option in a constantly evolving market.